2020
DOI: 10.4103/ijoy.ijoy_37_19
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the therapeutic benefits of Pranayama (yogic breathing): A systematic review

Abstract: Background: Pranayama (yogic breathing) has demonstrated numerous beneficial health effects. At present, there are no systematic reviews evaluating the beneficial health effects of pranayama alone as a practice. Aim: The aim of this study is to perform a systematic review about the beneficial health effects of pranayama. Methods: Data were obtained using a stepwise search process by searching the online PubMed, Web of Science, and SciVerse Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 28 publications
1
45
0
2
Order By: Relevance
“…Considering the effects of therapeutic yoga in breast cancer, yogic breathing (pranayama) has shown numerous beneficial health effects in breast cancer patients undergoing radiotherapy [ 69 ] or chemotherapy [ 70 ], with an improvement in quality of life and fatigue [ 71 ], findings also found in our review. These authors suggested, as a possible cause, that during controlled breathing exercises, the stretching of lung tissue produces inhibitory signals in the vagus nerve, which ultimately shifts the autonomic nervous system towards the parasympathetic domain, resulting in a calm and alert state of mind, coinciding with our review where a reduction in sensitivity to adverse physiological reactions and anxiety [ 54 ] was found.…”
Section: Discussionsupporting
confidence: 70%
“…Considering the effects of therapeutic yoga in breast cancer, yogic breathing (pranayama) has shown numerous beneficial health effects in breast cancer patients undergoing radiotherapy [ 69 ] or chemotherapy [ 70 ], with an improvement in quality of life and fatigue [ 71 ], findings also found in our review. These authors suggested, as a possible cause, that during controlled breathing exercises, the stretching of lung tissue produces inhibitory signals in the vagus nerve, which ultimately shifts the autonomic nervous system towards the parasympathetic domain, resulting in a calm and alert state of mind, coinciding with our review where a reduction in sensitivity to adverse physiological reactions and anxiety [ 54 ] was found.…”
Section: Discussionsupporting
confidence: 70%
“…Further, through systematically paying attention to sensations of breathing, yogic breathing may be aimed to improve metacognitive awareness of mind–body connections and interoception, which is fundamentally a process linking brain and body 62 . For a systematic review of therapeutic benefits of yogic breathing see Jayawardena et al 63 One commonly studied mechanism for the health benefits of yogic breathing is its balancing effect on the autonomic nervous system through parasympathetic activation 60 , 64 . Since CSF is sensitive to respiratory dynamics 12 14 , 37 , we believe another potential mechanism for the benefits of yogic breathing is its influence on pulsatile CSF dynamics, which to date has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It may be used to help patients with asthma, polyovarian cystic disease, MS, obesity, attention deficit, and sleep disorders. [ 42 43 44 45 46 47 ]…”
Section: Discussionmentioning
confidence: 99%